Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT Bank Mayapada KCP Majapahit Semarang - Mohamad Farrel Eka Wijaya; Ninik Dwi Atmini; Yoki Nawan Gunara (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine and explain the effect of work motivation on employee performance, the effect of work discipline on employee performance, and the effect of work motivation and work discipline together on employee performance. The population in this study were all employees of PT Bank Mayapada KCP Majapahit Semarang totaling 38 people, with the research technique using the census method. The data analysis technique used is multiple linear regression. The results showed that work motivation has a positive and significant effect on employee performance, work discipline also has a positive and significant effect on employee performance, and work motivation and work discipline jointly affect employee performance.